PROMOTING VOCATIONAL EDUCATION FOR GREEN JOBS: A STRATEGY FOR ACHIEVING CLIMATE CHANGE AND SOCIAL DEVELOPMENT GOALS (NAU Journal of Technology and Vocational Education, 2026)
This study explores the pivotal role of vocational education in fostering green jobs as a strategic approach to mitigate climate change and achieve sustainable development goals. As the world grapples with environmental degradation and social inequality, vocational education emerges as a critical tool in equipping individuals with the skills needed for sustainable practices and green industries. By focusing on areas such as renewable energy, sustainable agriculture, energy efficiency, and environmental conservation, vocational education can significantly contribute to reducing greenhouse gas emissions and promoting sustainable development. The study highlights the importance of developing relevant curricula, providing hands-on training, fostering industry-academia partnerships, and advocating for policy support to promote vocational education for green jobs. It also emphasizes the need for continuous improvement and adaptation to evolving green technologies and practices. Through a comprehensive review of existing literature and best practices, this study aims to provide insights into the potential of vocational education to drive sustainable development and climate action. By promoting vocational education for green jobs, governments, educational institutions, and industries can collaborate to create a more sustainable and resilient future. This study concludes that vocational education is a vital component of a holistic approach to achieving climate change and sustainable development goals, offering valuable skills and employment opportunities for individuals while contributing to the well-being of the planet.
Keywords: Green jobs; Climate change; Development goals; Vocational Education; Skills